2013
DOI: 10.1017/s0022215113002417
|View full text |Cite
|
Sign up to set email alerts
|

Parotid lymphoepithelial cysts in human immunodeficiency virus: a review

Abstract: Human immunodeficiency virus testing is recommended for patients with benign lymphoepithelial cysts, as this can often be the first indication of human immunodeficiency virus infection. Benign lymphoepithelial cysts are important diagnostic and prognostic indicators in human immunodeficiency virus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…As noted in the present case, the LCs usually appear solitary in the oral cavity, but there are reports of intraosseous bilateral LCs in jaw and palatine tonsils, and multiple cysts in the parotid gland region in patients affected by HIV, which is one of the signs of the virus infection [ 9 – 11 ]. Our group previously reported an unusual case of multiple LCs located in sublingual region in a patient without systemic involvement [ 15 ].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…As noted in the present case, the LCs usually appear solitary in the oral cavity, but there are reports of intraosseous bilateral LCs in jaw and palatine tonsils, and multiple cysts in the parotid gland region in patients affected by HIV, which is one of the signs of the virus infection [ 9 – 11 ]. Our group previously reported an unusual case of multiple LCs located in sublingual region in a patient without systemic involvement [ 15 ].…”
Section: Discussionmentioning
confidence: 80%
“…The mouth floor is the most affected site, followed by the lateral and ventral margin of the tongue [ 1 , 3 – 5 , 7 , 8 ]. Some cysts may also occur in the soft and hard palate, retromolar area, palatoglossus arch, palatine tonsil, jaw, and parotid gland, which may indicate, in this last case, an early infection by HIV [ 4 , 5 , 9 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated that CT findings of single and/or multiple parotid cysts and cervical adenopathy were sufficient for BLL diagnosis. 8 Parotid BLLs need to be distinguished clinically and pathologically from the lymphoepithelial sialadenitis of Sjögren syndrome, Warthin tumor, and Hodgkin lymphoma. This was particularly important for the first case given the patient's prior history of Hodgkin lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Reports in the literature suggest that these lesions typically appear as prominent round hypoechoic areas, ranging from 0.5 to 5 cm in diameter, with well circumscribed margins, internal septations, and posterior acoustic enhancement. 8,9 Multiple computed tomography (CT) images of the neck from the thoracic inlet to the skull base were obtained for further investigation to include surveillance for reoccurrence of her Hodgkin lymphoma. Computed tomography demonstrated peripherally enhancing cystic structure within the right parotid gland measuring 1.2 cm in diameter (Figure 2A).…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation